Advanced materials for clean energy - Xu, Qiang (Materials scientist); Kobayashi, Tetsuhiko (CRC Press, 2015)
Advanced Materials for Clean Energy surveys the key developments in the science and engineering of the state-of-the-art materials for clean energy. The book provides a broad overview of materials for photovoltaics, solar energy conversion, thermoelectrics, piezoelectrics, supercapacitors, rechargeable batteries, fuel cells, and hydrogen production and storage